Human-Computer Interaction: Design and Evaluation 17th International Conference, HCI International 2015, Los Angeles, CA, USA, August 2-7, 2015, Proceedings, Part I - Kurosu, Masaaki; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
The 3-volume set LNCS 9169, 9170, 9171 constitutes the refereed proceedings of the 17th International Conference on Human-Computer Interaction, HCII 2015, held in Los Angeles, CA, USA, in August 2015. The total of 1462 papers and 246 posters presented at the HCII 2015 conferences was carefully reviewed and selected from 4843 submissions. These papers address the latest research and development efforts and highlight the human aspects of design and use of computing systems. The papers in LNCS 9169 are organized in topical sections on HCI theory and practice; HCI design and evaluation methods and tools; interaction design; emotions in HCI.
HCI theory and practice -- HCI design and evaluation methods and Tools -- Interaction design -- Emotions in HCI.
Keywords: Computer science; Software engineering; Information storage and retrieval; User interfaces (Computer systems).; Artificial intelligence; Education -- Data processing; Multimedia systems; Computer Science; User Interfaces and Human Computer Interaction; Computers and Education; Media Design; Artificial Intelligence (incl. Robotics).; Information Storage and Retrieval; Software Engineering; Electronic books